Dynamic modelling of oil and water molecules of methylcellulose-coated fried potato during and in the post-frying condition - Lee, X.F.; Naim, M.N.; M. Azmi, N.S.; Mohammed, M.A.P.; Othman, S.H.; Abu Bakar, N.F.; Adam, F. (Rynnye Lyan Resources, 2025)
This work investigated the migration of the oil and water molecules in methylcellulose (MC)-coated and uncoated potatoes during and after the deep-frying process. The research aimed to understand how the MC layer prevented the oil uptake due to water migration from the substrate to cooking oil along the frying process using molecular dynamic modelling techniques and validated by the experimental work. During the frying process, the diffusion coefficient from the mean square displacement (MSD) value of water in the frying oil, Dw, at the interfacial of MC-coated showed a greater value compared to the uncoated ones with a diffusion coefficient of 1.08 and 0.63 (10-4 cm2/s), respectively. In the post-frying process, the Dw in the cooling frying oil was 0.94 and 0.08 (10-4cm2/s), respectively. Both coated and uncoated layers provide intense water flux against the oil penetration along the process. A consistently low diffusion coefficient of oil into starch, Do of 0.14 and 0.13 (10-4 cm2/s), was noticed during and in the post-frying process. Meanwhile, lower diffusion coefficient Dw values in uncoated samples were not caused by oil penetration but due to the large amounts of trapped surface oil known as structural oil in the crust layer. The evidence was shown by low Do in the uncoated potato's region with a diffusion coefficient during and after the frying process of 0.35 and 0.07 (10-4 cm2/s), respectively. The phenomenon was proven in the experimental work whereby more significant pore areas were noticed in uncoated ones compared with the MC-coating substrate of 25107 vs 24000 mm2, respectively, at various MC concentrations. Both the model and the experimental results agree on the significant trend of oil uptake reduction, as the MC layer promotes sufficient water flux out from the fried substrate to prevent oil penetration into the starch along the frying process.